BUILDING STUDENTS’ DIGITAL LITERACY SKILL THROUGH WEBLOG-LIBRARY CENTER APPROACH - Yunani Atmanegara (Jurnal Didascein Bahasa, 2019)
In connection with today’s digitalization era,the integration of ICT into English literacy learningneeds more concern from educators. Teachers are encouraged to explore the use of ICT and develop students’ digital literacy skill as well. This study used weblog-library center as one of alternative to use in literacy learning. This study involved forty students of the eleventh grade divided into experimental and control group. Both groups were given digital literacy questionnaire in the beginning and at the end of the studycovering four digital literacy components; basic ICT skills, information sources, digital competencies, andattitude and perspective toward digital usage and digital transformation. In addition, observation was conducted in experimental group to obtain clear information about students’ digital literacy progress. The questionnaire was analyzed by using paired and independent sample t-tests. Meanwhile, observation results were calculated using percentage analysis. The results indicate that weblog-library center could improve students’ digital literacy not only as the students perceived, but also as the teacher percieved. The experimental students could use digital tool properly and appropriately so that their ICT skill developed, the knowledge about getting information sources increased, digital competence enhanced and attitude and perspective about digital usage and transformation were positive.